Phytotoxic Effects of Non-ionic Surfactant Octylphenol Series (Triton X-100, Triton X-114, Triton X-405) on Onion - Dane, Feruzan; Yilmaz, Gulden; Akbas, Halide; Ozturk, Fatmanur; Leventer, Sinem (Asian Journal of Chemistry, 2012)
In this study, three widely used octylphenol series non-ionic surfactant Triton X-114, Triton X-100 and Triton X-405 were selected to examine their phytotoxic effects. They were evaluated under laboratory conditions using onion (Allium cepa L.) as a test material. The phytotoxic effects on root were determined after 7th days. Surfactants used in study were tested at three different surfactant concentrations, 5.00, 2.50 and 1.25 g/L (w/v) concentrations. The phytotoxicity results were based on the effective concentration that reduced root growth by 50 % (EC50). Some differences were observed between the effects of three types of surfactants. Stimulatory effects only occurred in Triton X-405 while inhibitory effects occured in Triton X-100 and Triton X-114 at all concentrations. It was observed that inhibitory effects increased with increasing concentrations of Triton X-114 and Triton X-100.